Two countries - one system of vocational education? : A comparison of the apprenticeship reform in the commercial sector in Switzerland and Germany - Pilz, Matthias [Verfasser] (My University, 2007)
"In both Switzerland and Germany, necessary reforms in vocational education have been taking place for the past few years. By taking a closer look at the commerce sectors of both countries and their reforms, one can better compare their systems of apprenticeship. While the necessity for change in the commercial sector was similar in both countries, the course of these changes has been quite different. A widespread reform of the Swiss commercial sector began in 2003. In Germany, a comparable sweeping change in commercial apprenticeships cannot be seen, although many reforms have been implemented. In order to analyse the process and results of modernisation of both vocational education systems, they are compared and contrasted. Finally, hypotheses are formed about the possible reasons for the differences in vocational education in these two countries." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; S 6.4.1 Kaufleute; T 1.5 International vergleichende Berufsbildungsforschung; I 2.1 Deutschland; I 2.2.1 Westeuropa; Duales System; Kaufmännische Ausbildung; Kaufmännischer Beruf; Reform; Internationaler Vergleich; Vergleichende Berufsbildungsforschung; Bundesrepublik Deutschland; Schweiz